Paper 26: Update On Performance And Return To Sport After Biceps Tenodesis In Professional Baseball Players. Issue 7 (30th July 2022) - Chalmers, Peter; D'Angelo, John; Ma, Kevin; Rowe, Dana; Ciccotti, Michael; Romeo, Anthony; Erickson, Brandon
Objectives: The purpose of this study was to determine the return to sport (RTS) rate and performance upon RTS in professional baseball players who underwent biceps tenodesis. A secondary purpose was to compare the postoperative performance of the group of players who underwent biceps tenodesis to a group of matched controls. Methods: All professional baseball pitchers who underwent biceps tenodesis between 2014 and 2017 were included. Players with concomitant rotator cuff repair were excluded. Demographic and performance data (preoperative and postoperative) were recorded for each player. Performance metrics were then compared between the biceps tenodesis and matched control (no history of biceps tenodesis) groups. Results: 14 players (average age 27±4 years; 12 pitchers, 2 position outfielders) were included. Most (79%) were open subpectoral tenodeses while two were arthroscopic biceps transfers, and one was an arthroscopic suprapectoral tenodesis. Fixation methods included cortical button (42%), interference screw (25%), suture anchor (25%) and drill holes (8%). Most players (79%) underwent concomitant procedures (43% underwent SLAP repairs). Among the 14 players, 2 were unable to RTS, 5 RTS but to a lower level, and 7 RTS at the same or a higher level. Thus, overall, while 86% (12/14) were able to RTS, 50% (7/14) RTS at the same or a higher level and 50% were either unable to return or returned to a lower level. Among pitchers, 100% (12/12) were able to RTS, but only 50% (6/12) were able to return to the same or a higher level. For those players who did return to play, it took 245±84 days, and their performance following RTP was unchanged and did not differ from matched controls. Conclusions: While 86% of professional baseball players returned to sport following biceps tenodesis, only 50% returned to the same or higher level. No decline in performance was noted in players who successfully returned. Open subpectoral tenodesis is the most common tenodesis technique performed on professional baseball players UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/c7753b55-d658-4847-a8e7-7b70c6cad84f/1/Table_1.docx UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/961efbc8-aedb-4cfe-b18f-6b8c07d93ec7/1/Table_2.docx UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/36fbb55a-f22f-468e-a8a3-e7a29979b4b8/1/Table_3.docx None